2008
DOI: 10.1002/jbm.a.31844
|View full text |Cite
|
Sign up to set email alerts
|

The in situ synthesis of biphasic calcium phosphate scaffolds with controllable compositions, structures, and adjustable properties

Abstract: In this study, biphasic calcium phosphate (BCP) porous scaffolds with controllable phase compositions, controllable macropore percentages, and thus adjustable properties were in situ prepared by sintering a series of composites consisted of calcium phosphate cement (CPC) and porous resin negative mold made from rapid prototyping (RP) technique. The CPC pastes were formed by mixing a powder mixture of tetracalcium phosphate and anhydrous dicalcium phosphate with liquid phase of diluted phosphate acid solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…All others reported observing either a peak in strength [55,71,72] or simply a decrease in strength [50,57,61]. The data from Metsger et al [74], which reported the increase in strength, are not included in Fig.…”
Section: The Effect Of B-tcp On the Strength Of Bcp Composite Scaffoldsmentioning
confidence: 90%
See 2 more Smart Citations
“…All others reported observing either a peak in strength [55,71,72] or simply a decrease in strength [50,57,61]. The data from Metsger et al [74], which reported the increase in strength, are not included in Fig.…”
Section: The Effect Of B-tcp On the Strength Of Bcp Composite Scaffoldsmentioning
confidence: 90%
“…3 because the paper does not provide specific data points. Habibovic et al [72], Guo et al [71] and Raynaud et al [55] showed maximum strengths at approximately 20, 40 and 10 wt.% b-TCP, respectively. In contrast, Miranda et al [70], Shiota et al [63] and Ruys et al [73] all showed a monotonic decrease in strength.…”
Section: The Effect Of B-tcp On the Strength Of Bcp Composite Scaffoldsmentioning
confidence: 95%
See 1 more Smart Citation
“…If the coating material is dissolved too fast, before the growth of bones or the equilibrium of the implants, the coating is simply worthless. The dissolution rate of HAp is very slow in vivo and may take years to be resorbed [14].β-TCP is chemically stable and has a fairly fast bio resorption rate [15].These reasons justify the development of BCP coatings to achieve the anticipated dissolution rate [16].Many coating techniques such as plasma spraying [17], dip coating [18], sputter coating [19], bio mimetic coating [20], and electrodeposition [21] have been employed to coat ceramics on metal implants.…”
Section: *Manuscriptmentioning
confidence: 98%
“…Among various CPs, hydroxyapatite [HAp, Ca 10 (PO 4 ) 6 (OH) 2 ] and β-tricalcium phosphate [β-TCP, Ca 3 (PO 4 ) 2 ] are most commonly used ones. The high degradation rate of β-TCP makes it difficult to match with the new bone growth rate 4. Some research has been reported on biphasic calcium phosphates (BCPs), consisting of HAp and β-TCP, in which degradation rate can potentially match the new bone growth rate 5-8.…”
Section: Introductionmentioning
confidence: 99%